Americanismos de la grastronomía en la lexicografía italoespañola actual. - ARIOLFO, ROSANA (Scripta)
The present study analyzes quantitatively and qualitatively the treatment of American gastronomic cultural words lemmatized in the three most recent and large Italian-Spanish bilingual dictionaries, i.e. Garzanti (2018), Zanichelli (2020) and Hoepli (2021). Specifically, and after terminologically defining cultural words in the field of bilingual lexicography, this paper aims, first, to quantify and classify by typology and area of origin the Americanisms belonging to the field of food that are collected in the mentioned works. Secondly, we will analyze what metalexicographical treatment has been given to these cultural words in the three mentioned dictionaries, that is, if they offer translation equivalents, or if they provide cultural definitions or encyclopedic explanations, in order to determine what kind of communicative activities the adopted solutions can help to solve.